Bibliometric study of research on electoral campaigns in scientific communication journals (2012-2022) - Figuereo-Benítez, Juan C.; Moreno Espinosa, Pastora; Mancinas-Chávez, Rosalba (Revista General de Información y Documentación, 2024)
In the field of communication research, there is a substantial collection of scientific texts that have contributed to the analysis of a complex and ever-evolving human phenomenon. Although this literature has been extensively explored, there is one specialty that has yet to receive adequate attention: the scientific production focused on the study of electoral campaigns, which play a crucial role in democratic regimes, particularly in periods of polarisation and declining trust. This article aims to present a specific bibliometric analysis of scientific studies on electoral campaigns published in the most influential Spanish scientific communication journals over the past decade (2012-2022), as well as emerging trends in this field. The sample includes 274 articles published during the last decade that address electoral campaigns from a communicative perspective. Using quantitative bibliometric analysis techniques, a range of variables has been examined, including publication dates, language, authorship and institutional affiliations, keywords, geographical scope, year and country of the elections studied, topics covered, citations received, and methods used. The results reveal a preference for quantitative techniques, especially content analysis, in this scientific production. Additionally, it is observed that articles are predominantly authored by individuals affiliated with public universities, and in recent years, there has been a significant increase in the analysis of social media platforms such as Facebook and Twitter in the context of electoral campaigns.